Group Counseling of Cognitive Behavior with Self Instruction Technique On Self Efficacy and Academic Burnout (Jurnal Bimbingan Konseling, 2019)
This study aims to prove that group counseling with self instruction technique is effective to enhance self efficacy and reduce academic burnout. The design employed was pre-test – post-test control group. The subject of the study was selected by using purposive sampling technique as many as 16 students. To place the subject in the experimental group and control group, random assignment was conducted so that there were 8 students in each group. The result of MANOVA test proved that group counseling with self instruction effectively enhanced self efficacy (F3.12 = 185.787; ηp2 = 0.979; p < 0.01) and reduced academic burnout (F3.12 = 308.938; ηp2 = 0.987; p < 0.01). In addition, the Paired Sample t-test showed a result that there was enhancement of self efficacy (t = -19.943; p < 0.01) and significant decrease in academic burnout (t = 23.213; p < 0.01) in the experimental group. Meanwhile, the enhancement of self efficacy (t = -0.424; p > 0.05) and the decrease in academic burnout (t = 0.552; p > 0.05) in the control group did not significantly occur. This study obtained the findings that group counseling with self instruction technique effectively enhances self efficacy and reduces academic burnout.This study aims to prove that group counseling with self instruction technique is effective to enhance self efficacy and reduce academic burnout. The design employed was pre-test – post-test control group. The subject of the study was selected by using purposive sampling technique as many as 16 students. To place the subject in the experimental group and control group, random assignment was conducted so that there were 8 students in each group. The result of MANOVA test proved that group counseling with self instruction effectively enhanced self efficacy (F3.12 = 185.787; ηp2 = 0.979; p < 0.01) and reduced academic burnout (F3.12 = 308.938; ηp2 = 0.987; p < 0.01). In addition, the Paired Sample t-test showed a result that there was enhancement of self efficacy (t = -19.943; p < 0.01) and significant decrease in academic burnout (t = 23.213; p < 0.01) in the experimental group. Meanwhile, the enhancement of self efficacy (t = -0.424; p > 0.05) and the decrease in academic burnout (t = 0.552; p > 0.05) in the control group did not significantly occur. This study obtained the findings that group counseling with self instruction technique effectively enhances self efficacy and reduces academic burnout.